Adjudication of Coreference Annotations via Answer Set Optimization - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
We describe the first automatic approach for merging coreference annotations obtained from multiple annotators into a single gold standard. Merging is subject to hard constraints (consistency) and optimization criteria (minimal divergence from annotators) and involves an equivalence relation over a large number of elements. We describe two representations of the problem in Answer Set Programming and four objective functions suitable for the task. We provide two structurally different real-world benchmark datasets based on the METU-Sabanci Turkish Treebank, and we report our experiences in using the Gringo, Clasp, and Wasp tools for computing optimal adjudication results on these datasets.
Keywords: Coreference resolution; Adjudication; Answer set programming; PROGRAMS